Strategic Surrender : The Politics of Victory and Defeat - Kecskemeti, Paul (California Stanford University Press, 1958)
Analysis of strategic surrender as a problem in political theory. Presents case studies of the 4 major surrenders of World War 2 and speculates on the relevance of this experience in a thermonuclear age.
Include Bibliography and index
Keywords: World War (1939-1945) -- Capitulations, Military